Diabetic foot infections: state‐of‐the‐art. Issue 4 (1st September 2013) - Uçkay, I.; Gariani, K.; Pataky, Z.; Lipsky, B. A.
<x xml:space="preserve">Abstract</x> Foot infections are frequent and potentially devastating complications of diabetes. Unchecked, infection can progress contiguously to involve the deeper soft tissues and ultimately the bone. Foot ulcers in people with diabetes are most often the consequence of one or more of the following: peripheral sensory neuropathy, motor neuropathy and gait disorders, peripheral arterial insufficiency or immunological impairments. Infection develops in over half of foot ulcers and is the factor that most often leads to lower extremity amputation. These amputations are associated with substantial morbidity, reduced quality of life and major financial costs. Most infections can be successfully treated with optimal wound care, antibiotic therapy and surgical procedures. Employing evidence‐based guidelines, multidisciplinary teams and institution‐specific clinical pathways provides the best approach to guide clinicians through this multifaceted problem. All clinicians regularly seeing people with diabetes should have an understanding of how to prevent, diagnose and treat foot infections, which requires familiarity with the pathophysiology of the problem and the literature supporting currently recommended care.